Analysis of Mood and Speech Function Found in “La La Land 2016” Movie - Ika Shakila Maharani; Nargis; Ikhfi Imaniah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the utilization of mood and speech functions in the dialogues of the romantic musical movie La La Land (2016). Employing a qualitative descriptive method, the research focused on identifying and analyzing different types of Mood (declarative, interrogative, imperative) and Speech Functions (expressive, directive, referential, metalinguistic, poetic, phatic) within selected dialogues of the main characters. Data were collected through meticulous observation and transcription of movie dialogues, followed by systematic classification and interpretation based on Halliday & Matthiessen’s (2014) and Holmes’ (2013) frameworks. The findings reveal that the Declarative Mood is the most dominant mood type, accounting for 10 out of 15 total mood instances. This prevalence suggests that characters frequently engage in conveying information about their feelings, experiences, and plot developments. Concurrently, the Referential function emerged as the most dominant speech function, with 8 out of 27 total speech functions. This indicates a primary focus on providing information, describing events, and stating facts essential for advancing the narrative and establishing context within the film's dialogues. The study highlights how these linguistic elements contribute to the emotional delivery and narrative messages of La La Land, offering insights into the complex interplay between language, character dynamics, and thematic exploration in musical movies.